2016
DOI: 10.18869/nrip.ptj.6.3.169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracorporeal Shock Wave Therapy on Muscle Spasticity in Post-Stroke Patients: An Ultrasonography and Clinical-Base Study

Abstract: Purpose:To investigate the effect of single session Extracorporeal Shock Wave Therapy (ESWT) over the ankle plantar flexor muscles on the spasticity, muscle architecture, and gait in chronic stroke patients. Methods:This quasi-experimental, single group study had a repeated measures design. A total of 17 post-stroke patients were selected by convenience sampling method, and received 2000 shots of ESWT on the ankle plantar flexor muscles of the affected side in one session. Outcome measures consisted of Modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…For the PA and MT, mean scores were decreased after ESWT treatment. These finding are similar to those from another study that showed ESWT can change the scores of MFL, MT, and PA [16].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…For the PA and MT, mean scores were decreased after ESWT treatment. These finding are similar to those from another study that showed ESWT can change the scores of MFL, MT, and PA [16].…”
Section: Discussionsupporting
confidence: 91%
“…It is known that muscle fascicular change is important as an underlying mechanism for spasticity. The correlation between the spasticity score and muscle architecture of the spastic medial gastrocnemius muscle has been shown in previous studies . In the present study, we analyzed the correlation between the changes in muscle architecture and the changes in clinical measures.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations